Alginate-assistant nanofiber integrated with polypropylene hernia mesh for efficient anti-adhesion effects and enhanced tissue compatibility. (15th April 2022) - Mao, Ying; Meng, Yunxiao; Li, Shaojie; Li, Yan; Guidoin, Robert; Wang, Fujun; Qiao, Yansha; Brochu, Gaetan; Zhang, Ze; Tang, Jianxiong; Wang, Lu
Abstract: Polypropylene (PP) mesh has been one of the most frequently selected materials for abdominal wall hernia (AWH) repair in the past decades. However, the repair effectiveness is often compromised by the high incidence of adverse events. Improvements are highly desirable to reduce unwanted visceral adhesion and increase tissue integration. Herein, we developed a PP-based composite mesh combined with alginate-assistant nanofiber membrane (NFM) by assembling a large-pore lightweight PP mesh, a NFM barrier consisting of poly (lactic-co-glycolic acid) (PLGA) and polycaprolactone (PCL), and an alginate hydrogel (AH). In vitro studies revealed that the resulting meshes had excellent structural stability, mechanical properties, and biocompatibility. The NFM barriers were firmly attached to the PP substrates, with AH effectively eliminating the delamination without unwanted damage to the nanofiber barrier. In vivo experiments showed that incorporating AH-assistant NFM into PP prostheses could prevent visceral adhesion in an effective manner and promote mesh integration into surrounding tissues from the abdominal wall. These results prove a novel facile and successful strategy to endow prosthetic meshes with superior anti-adhesion capability and tissue compatibility for repairing AWH. Graphical abstract: Image 1 Highlights: Nanofiber membranes (NFM) composed of PLGA and PCL were proved to be a promising physical barrier. The resulting NFM barrier combining alginate layer was integrated into PP substrate to produce new composite meshes. The obtained composite mesh showed efficient anti-adhesion capability and superior tissue compatibility. Combining alginate-assistant NFM barrier and PP mesh provides a strategy to customize anti-adhesive hernia meshes.